Polymethacrylate Sphere-Based Assay for Ultrasensitive miRNA Detection - Samira Hosseini; Patricia Vázquez-Villegas; Richard C. Willson; Marco Rito-Palomares; Margarita Sanchez-Dominguez; Leo H. Koole; Marc J. Madou; Sergio O. Martínez-Chapa (Advances in Polymer Technology)
Although microRNAs (miRNAs) have emerged as increasingly important target analytes, their biorecognition remains challenging due to their small size, high sequence homology, and low abundance in clinical samples. Nanospheres and microspheres have also gained increasing attention in biosensor applications due to their high specific surface area and the wide variety of compositions available. In this study, chemically designed and synthesized microspheres with active functional groups were used to promote effective miRNA immobilization resulting in better biorecognition. Upon conjugation with fluorescence-labeled complimentary probes, acylate-based spheres have indirectly detected MiR159, offering significantly enhanced analytical sensitivity, specificity, and accuracy while yielding a considerably low limit of detection (LOD) of 40 picomolar. Furthermore, MiR159 presence, which is known to be inversely correlated to breast cancer incidence and progression, was successfully detected in a competitive assay, which is promising for upgrading the current assay to clinical use.